Data for Freshwater mollusc community screening - classical and eDNA monitoring to detect rare, indicator and invasive species - Leidenberger, Sonja; Wiese, Vollrath; Schaumann, Finja; Pleiss, Felix; Langen, Kathrin; Bourlat, Sarah J. (University of Skövde, 2024)
The data belongs to the study Freshwater mollusc community screening - classical and eDNA monitoring methods to detect rare, indicator and invasive species. Tables and figures represent in detail the sample localities of 15 Swedish lakes and rivers. The study was focusing on Plankton samples and two kind of sediment samples (Kick-net and M42 method) at two sampling times (spring and autumn). Species were found through a) classical morphological studies where freshwater molluscs were determined by hand with a stereoscopic microscope; b) with barcoding by the cytochrome c oxidase subunit I (COI) gene and c) through eDNA metabarcoding analysis (Illumina sequencing). The main focus was on pea clams, but even other benthic freshwater molluscs and organisms could be detected.
COI barcode data were analyzed for a Barcode Tree with MEGA version 11.0.13 (https://www.megasoftware.net/) (Stecher et al., 2020). Metabarcoding data were analyzed with the Apscale pipeline (https://github.com/DominikBuchner/apscale, Buchner et al., 2022).

Uppgifterna tillhör studien Freshwater mollusc community screening - classical and eDNA monitoring methods to detect rare, indicator and invasive species. Tabeller och figurer representerar i detalj resultat från provorterna för 15 svenska sjöar och älvar. Studien fokuserade på planktonprover och två sorters sedimentprover (Kick-net och M42 metoden) vid två provtagningstillfällen (vår och höst). Arter hittades genom a) klassiska morfologiska studier där sötvattensmollusker bestämdes för hand med ett stereolupe; b) med streckkodning av cytochrome c oxidase subunit I (COI) och c) genom eDNA metabarcoding analys (Illumina sekvensering). Huvudfokus låg på ärtmusslor, men även andra bentiska sötvattensmollusker och organismer kunde påvisas. COI streckkodsdata analyserades för ett streckkodsträd med software MEGA version 11.0.13 (https://www.megasoftware.net/) (Stecher et al., 2020). Metabarcoding data analyserades med software Apscale pipeline (https://github.com/DominikBuchner/apscale, Buchner et al., 2022).
Data för Freshwater mollusc community screening - classical and eDNA monitoring to detect rare, indicator and invasive species
Keywords: FRESHWATER ECOSYSTEMS; Bio-geographical regions; Biogeografiska regioner; Habitats and biotopes; Naturtyper och biotoper; Species distribution; Arters utbredning; benthic macroinvertebrates; bentiska evertebrater; eDNA metabarcoding; eDNA metabarcoding; pea clams; ärtmusslor; Sweden; Sverige; rare species; sällsynta arter; invasive species; invasive främmande arter; freshwater bivalves; sötvatten musslor; indicator species; indikator arter; freshwater monitoring; sötvatten övevakning; barcoding; barcoding; Sphaeriidae; Pisidium; Veneroida; Bivalves; Euglesa; Odhneripisidium; Biological Sciences; Biologi; Zoology; Zoologi; Ecology; Ekologi; Biota; Biologi och ekologi; Molecular Biology; Molekylärbiologi